Dissolution corrosion of 4H‐SiC in lead‐bismuth eutectic at 550°C. Issue 10 (24th May 2019) - Li, Bingsheng; Sheng, Yanbin; Liu, Huiping; Lu, Xirui; Shu, Xiaoyan; Xiong, Anli; Wang, Xu
Abstract: The corrosion behavior of 4H‐SiC in lead‐bismuth (Pb‐Bi) eutectic (LBE) at 550°C is investigated. To clarify the effect of irradiation damage on corrosion, samples with and without Si 5+ ion irradiation are contrastively evaluated. The main results show that dissolution corrosion occurs in both unirradiated and irradiated samples, while the irradiation damage can accelerate the corrosion rate. The corroded surface is characterized by the loss of C element and the formation of amorphous layers with a slight enrichment of Si atoms. The possible reasons are discussed. Abstract : The corrosion behavior of 4H‐SiC in lead‐bismuth (Pb‐Bi) eutectic (LBE) at 550°C was investigated. To clarify the effect of irradiation damage on corrosion, samples with and without Si 5+ ion irradiation were contrastively evaluated. The main results show that dissolution corrosion occurs in both unirradiated and irradiated samples, while the irradiation damage can accelerate the corrosion rate.